2018
DOI: 10.1186/s12876-018-0912-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of intrahepatic cholangiocarcinoma after curative resection: outcome, prognostic factor, and recurrence

Abstract: BackgroundIntrahepatic cholangiocarcinoma (ICC) is a relatively rare subtype of cholangiocarcinoma. The study herein gathered experience of surgical treatment for ICC, and aimed to analyze the prognosis of patients who had received curative-intent liver resection.MethodsA total of 216 patients who had undergone curative-intent liver resection for ICC between January 1977 and December 2014 was retrospectively reviewed.ResultsOverall, the rates of 5-years recurrence-free survival (RFS) and overall survival (OS) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
38
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 22 publications
1
38
2
1
Order By: Relevance
“…Comparatively speaking, fewer studies report the meaning of PNI to RFS. As far as we concerned, only studies from Kang et al [31] and Chan et al [32] showed PNI had no influence in RFS through the univariate and multivariate analyses in their case-control studies, which are not consistent with our results. However, we did go further by using study design of historical cohort, K-M curves and the univariate and multivariate analyses to make a more convincible evidence.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Comparatively speaking, fewer studies report the meaning of PNI to RFS. As far as we concerned, only studies from Kang et al [31] and Chan et al [32] showed PNI had no influence in RFS through the univariate and multivariate analyses in their case-control studies, which are not consistent with our results. However, we did go further by using study design of historical cohort, K-M curves and the univariate and multivariate analyses to make a more convincible evidence.…”
Section: Discussioncontrasting
confidence: 99%
“…Ahn et al [30] retrospectively analyzed 292 R0-resected ICC patients and the univariate and multivariate survival analyses of OS showed PNI as an independent significant risk factor against long-term survival, which is consistent with our results. However, some studies revealed quite different results that did not support PNI as one [31,32]. Comparatively speaking, fewer studies report the meaning of PNI to RFS.…”
Section: Discussionmentioning
confidence: 95%
“…CCA is a deadly cancer worldwide waiting for innovative biomarkers and therapeutic strategies to improve the survival of patients 1,2 . In iCCA, several clinical variables have been identified as important prognostic factors after surgical resection for curative intent, including tumor size, pathological lymph node involvement and vascular invasion 1,29,30 . Omics approaches (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, the current patient underwent right hepatectomy and received systemic chemotherapy; she was successfully discharged and has been followed without further thrombosis during the 6 months after surgery. Because most patients of Trousseau's syndrome and intrahepatic cholangiocarcinoma are at an advanced stage by the time of diagnosis, it is difficult for them to undergo curative treatment [2,3,7,9]. Therefore, the prognosis of the patients with Trousseau's syndrome and intrahepatic cholangiocarcinoma is very poor [3,7,8].…”
Section: Discussionmentioning
confidence: 99%